VOLODYMYR VYNNYCHENKO’S DIARY: LINGUISTIC AND STYLISTIC NOTES - Kononenko, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Linguo-personal features of diary entries of the Ukraine statesman and politician, writer Volodymyr Vynnychenko, autocommunicative orientation of his text, elitist ability of the author’s linguistic personality to reflect complex social processes, inseparable from the issues of private life, are considered. The defining features of the writer’s idiosyncrasy are journalism, polemics, philosophical, heightened emotionality, and artistic worldview. The key internal words of the compositional purpose are Ukraine and the names that are part of the relevant conceptual and semantic field. Linguistic and stylistic unity of the narrative is achieved by individualized characteristics of the manner of writing, the reproduction of centrifugal psychosomatic parameters of the author’s personality, mediated by the influence of artistic linguistic thinking. In the pragmatic dimension, the texts of Vynnychenko’s notebooks, on the one hand, reproduce the diary genealogy established in personology, taking into account the figure of the writer, on the other hand, reflect the different structure of texts representing the author’s linguistic-poetic dissimilarity with other diarists. The diary entries include, in particular, descriptions of the environment with a focus on the Ukrainian-centric perception of nature in times of emigration, appeals to reflections on the mental type of Ukrainians, their ethnocultural traditions. Separate notes on the writer’s creative ideas, made as dramatic remarks, brief descriptions of the content of future plays. Records of personal life take the form of intimate speech, sustained in the perspective of restrained expression of feelings and experiences in the field of personal life. Functional and semantic analysis of Vynnychenko’s notebooks testifies to the high speech culture, artistic flair, peculiar features of thewriter’s idiosyncrasy.